Acute kidney injury in a Malaysian intensive care unit: assessment of incidence, risk factors and outcome - Md Ralib, Azrina; Mat Nor, Mohd Basri (World Federation of Societies of Intensive and Critical Care Medicine (WFSICCM), 2015)
Purpose Acute Kidney Injury (AKI) is common and carries a high mortality rate. Most epidemiological studies were retrospective and were done in Western populations. We aim to assess its incidence utilising both urine output and creatinine criteria, and its association with risk factors and outcome.